«Razón y cuenta que avia de dar al Inga quando bolviese del otro mundo»: ¿Trazas del Inkarrí en la Miscelánea austral de Dávalos y Figueroa (1602)? - Ajens, Andrés (Pontificia Universidad Católica del Perú, 2026)
We offer a literary, historical and philological analysis, of a story from the Miscelánea austral of Diego Dávalos and Figueroa (Lima, 1602), to assess its plausibility as well as its veracity, in view of the fact that one of the recurrent motifs of the so-called myths of the Inkarrí (s. XX), the eventual return of the Inca, appears here for the first time in a historical source. Analysis reveals a high degree of veracity, as well as some issues around plausibility. Taken together, this allows for a double articulation (Abercrombie) that operates within the story, as well as a double bind (Derrida) between the literary and ethnographic story.

Ofrecemos un análisis literario, histórico y filológico de un relato de la Miscelánea austral de Diego Dávalos y Figueroa (Lima, 1602), a fin de aquilatar su verosimilitud como su veracidad, en vista de que en él comparece por vez primera uno de los motivos recurrentes de los llamados mitos del Inkarrí (s. XX): el eventual retorno del Inca. Los análisis muestran un alto grado de veracidad, así como algunos problemas de verosimilitud. Con todo, ello permite dar cuenta de una articulación doble (Abercrombie) que opera al interior de dicho relato, así como de un double bind (Derrida) entre relato literario y etnográfico.
«Razón y cuenta que avia de dar al Inga quando bolviese del otro mundo»: Traces of the Inkarrí in the Miscelánea austral by Dávalos y Figueroa (1602)?
Keywords: Miscelánea austral; Inkarrí myths; Xauxa valley; Double articulation; Double bind; Miscelánea austral; Mitos del Inkarrí; Valle de Xauxa; Articulación doble; Double bind; https://purl.org/pe-repo/ocde/ford#6.01.01